Análise de lucratividade entre o mercado real e mercado financeiro da soja - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Brazilian agribusiness has been growing every year, according to CONAB data, commercialization and investments in soy are predominant in the real market, but its price is based on the financial market in the stock market. This work aims at analyzing the real market's profitability by the investor as an alternative to multiply its capital through the commercialization of its own grain production. In the financial market, the investor applies its financial resources in future soybean contracts, in order to ensure the appreciation of the price of the commodity in the future, thus guaranteeing a possibility of capital gain on the expiration date of the contract. The work 's outline has as its starting point the historical history of soybean prices in the financial market and the real market in the last ten years, more precisely in the period from 07/2008 to 07/2018. Information on the physical market in relation to production, production costs and soybean yields were obtained from the National Supply Company and the Department of Rural Economy. Regarding the financial market, the data were provided by Brazil Bolsa Balcão and by the Luiz de Queiroz Higher School of Agriculture. The set of information of both markets was treated with techniques of analysis of investments, which are: NPV (Net Present Value); TMA (Minimum Attraction Rate); PlayBack (Time to Return on Investment); Internal Rate of Return (IRR), based on the SELIC (Base Interest Rate of Interest) interest rate. The annual result of the invested capital investment suffered both positive and negative fluctuations in both markets, although the physical market had a higher financial result than the negative financial market. The values were obtained through the internal rate of return (IRR) method, which for the real market was 2.74% per year and a capital gain of 31.06% and for the financial market the loss was -15, 97% per annum with capital loss of -81.92% in the ten year period for both markets.
Keywords: Engenharia econômica; Mercado financeiro; Lucro; Soja; Economic engineering; Profit; Soy; Financial market; CNPQ::ENGENHARIAS